DEVELOPMENT OF UNCLEAR CRITERIA FOR DETERMINING THE SIGNIFICANCE OF A COMPOSITE SOCIAL PROFILE INFORMATION - Mozhaiev, Mykhailo; Buslov, Pavlo; Shvedun, Viktoriia (Ukrainian Information Security Research Journal, 2023)
The results of development of fuzzy criteria for determination of significance of composite information of social profile are presented. The simulation is carried out using OSINT technology - the technology of legal acquisition and use of information from open sources. As a result of the research, the parameters affecting the significance of individual characteristics of the social profile are selected and their characteristics are determined. The information of varying degrees of structurality is processed in the course of performing of the task of social profiling. At the same time, the following data models are used: network one - for storing the data of the final social profile, and presenting them in the form of graphs; relational one - for storing the information map of the social profile; post-shooting and NoSQL one - for storing unstructured source data and dynamic content, including multimedia. The conceptual model of presentation of these social profiles can be expanded and brought into line with the complex and mathematical models of the digital social environment. In the future, it is necessary to disclose the elements and relationships of the four basic categories of the infological model of presenting the results of social profiling. A new model of fuzzy significance coefficient of social profile parameters is obtained, the difference of which is the possibility of taking into account both formalized objective and difficult-to-interpret subjective indicators for evaluating the initial information of the SP. The advantage of using the significance criterion over the involvement of experts is the lower time spent on analyzing large amounts of data while maintaining the level of objectivity of the assessment. Consideration the diversity of the digital social environment is the next step.